Room-temperature stable loop-mediated isothermal amplification LAMP reagents to detect leptospiral DNA - Lee, Pui Yuei; Wong, Yien Ping; Othman, Shuhaidah; Chee, Hui Yee (Sciendo, 2021)
Loop-mediated isothermal amplification (LAMP) is one of the most promising tools for rapidly detecting Leptospira spp. However, LAMP is hampered by cold storage to maintain the enzymatic activity of Bst DNA polymerase. To overcome the drawback of cold storage requirement for LAMP reagents we modified the reagents by adding sucrose as stabilizer. We then sought to determine the stability at room temperature of the premixed LAMP reagents containing sucrose. Premixed LAMP reagents with sucrose and without sucrose were prepared. The prepared mixtures were stored at room temperature for up to 60 days, and were subjected to LAMP reactions at various intervals using rat kidney samples to detect leptospiral DNA. The premixed LAMP reagents with sucrose remained stable for 45 days while sucrose-free premixed LAMP reagents showed no amplification from day 1 of storage at room temperature up to day 14. The LAMP reagent system can be refined by using sucrose as stabilizer, thus allowing their storage at room temperature without the need for cold storage. The modified method enables greater feasibility of LAMP for field surveillance and epidemiology in resource-limited settings.